The Effect of QRIS Payment on Consumer Purchase Decisions Using Technology Acceptance Model - Zalukhu, Sukmardin; Sembiring, Falentino (Research Horizon, 2025)
This study aims to determine the influence of the use of the Quick Response Code Indonesian Standard (QRIS) digital payment method on consumer purchase decisions using the Technology Acceptance Model approach. There are three independent variables used in this study, namely perception of utility, attitude towards use, and intention to use, and one dependent variable, namely purchase decision. The research method used was quantitative with a survey approach, and data collection was carried out through a closed questionnaire of 400 respondents. Data analysis was carried out using the Partial Least Squares - Structural Equation Modeling method through SmartPLS. The results showed that all independent variables had a significant effect on purchasing decisions. The intention to use QRIS is the most dominant factor influencing purchase decisions, followed by attitudes towards its use and the perception of benefits. The R-Square value of 0.858 indicates that the research model has a strong clear power in explaining the variables of purchasing decisions. This research contributes to adoption of digital payment technology among consumers. The results of the research are expected to be considered for digital payment system developers, business actors, and researchers in developing more effective strategies to increase the use of QRIS.